2021
DOI: 10.1002/acm2.13156
|View full text |Cite
|
Sign up to set email alerts
|

Initial testing of pegfilgrastim (Neulasta Onpro) on‐body injector in multiple radiological imaging environments

Abstract: PurposeAn increasing number of implantable or external devices can impact whether patients can receive radiological imaging examinations. This study examines and tests the Neulasta (pegfilgrastim) Onpro on‐body injector in multiple imaging environments.MethodsThe injector was analyzed for four imaging modalities with testing protocols and strategies developed for each modality. In x‐ray and computed tomography (CT), scans with much higher exposure than clinical protocols were performed with the device attached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Partial electrical reset safety features were activated in two models at maximum doses but not at typical dose levels, and no devices were permanently damaged. A subsequent study on the impact of CT scans on a pegfilgrastim on-body injector at a much higher radiation dose than in routine scans found no sign of device error during or after the scans 68 . Based on available evidence over many years, the FDA determined that, even with the small number of reports of adverse effects received, little evidence existed that CT exposure was the cause of those events.…”
Section: Ct Safety Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial electrical reset safety features were activated in two models at maximum doses but not at typical dose levels, and no devices were permanently damaged. A subsequent study on the impact of CT scans on a pegfilgrastim on-body injector at a much higher radiation dose than in routine scans found no sign of device error during or after the scans 68 . Based on available evidence over many years, the FDA determined that, even with the small number of reports of adverse effects received, little evidence existed that CT exposure was the cause of those events.…”
Section: Ct Safety Considerationsmentioning
confidence: 99%
“…A subsequent study on the impact of CT scans on a pegfilgrastim on-body injector at a much higher radiation dose than in routine scans found no sign of device error during or after the scans. 68 Based on available evidence over many years, the FDA determined that, even with the small number of reports of adverse effects received, little evidence existed that CT exposure was the cause of those events. The FDA concluded that the probability of an adverse event occurring as a result of exposing implantable or wearable electronic medical devices to radiation during a CT scan was extremely low and that the clinical benefit of a medically indicated CT examination greatly outweighed the potential risk.…”
Section: Effects On Electronic Medical Devicesmentioning
confidence: 99%